Improving Students Learning Outcome of Geography Subject Through Cooperative Learning Model Type Group Investigation At XII IPS 1 Class in Sma N 1 Situjuah District - Elfada, Fetri; W, Agung Prasetyo (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
ABSTRACT : 21st Century learning requires educators to evaluate the implementation of learning in schools. The implementation of learning conducted by educators is currently not optimal in preparing students to face the challenges of the 21st century. This study aims to obtain information and discuss efforts to improve learning outcomes in geography through cooperative learning models of group investigation type in class XII IPS 1 Senior High School 1 Situjuah District. The research carried out is class action research (Classroom Action Research). This research was conducted in the even semester of the 2018-2019 school year starting from January to February 2019 with 4 meetings divided into 2 cycles. Cycle I had 2 meetings and Cycle II had 2 meetings. Subjects in this study were students of class XII IPS 1 at SMAN I Situjuah District with a total of 24 students. This research procedure consists of four stages, namely planning, implementation, observation, and reflection. Data collection techniques using observation, tests, and documentation. Data were analyzed using percentages and data reduction. The results showed that there was an increase in geography learning outcomes through cooperative learning models of group investigation type class XII IPS 1 SMAN 1, Situjuah District